Automatic classification of laparos call and playback tests at cuniculture nests - Souza Filho, Nilson Evilásio; Souza, Vinícius Mourão Alves de; Klinger, Ana Carolina Kohlrausch; Toledo, Geni Salete Pinto de (Ciência e Natura, 2018)
The vocal behavior of rabbit pups was monitored during their first 15 days of life. It was possible to estimate the average of vocalizations issued in the nest by correlation calculations applied to spectrographic images. We performed experimental tests of playback and observed the behavior between the offspring and the doe during the period of lactation. The vocalizations can be important in pup recognition and consequently, stimulate the doe to nurse their offspring, decreasing the rate of mortality in the breeding phase.